2006
DOI: 10.1158/0008-5472.can-06-1574
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Annexin A7 and p53 on Arachidonate Lipoxygenation in Prostate Cancer Cells Involve 5-Lipoxygenase Transcription

Abstract: Tumor suppressor function for Annexin A7 (ANXA7; 10q21) is based on cancer-prone phenotype in Anxa7(+/À) mouse and ANXA7 prognostic role in human cancers. Because ANXA7-caused liposome aggregation can be promoted by arachidonic acid (AA), we hypothesized that the phospholipid-binding tumor suppressor ANXA7 is associated with AA cascade. In a comparative study of ANXA7 versus canonical tumor suppressor p53 effects on AA lipoxygenation pathway in the p53-mutant and androgen-insensitive DU145 prostate cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
2
19
1
Order By: Relevance
“…The hnRNPK level within the nuclear matrix in particular correlates with the Gleason score in prostate cancer (Barboro et al, 2009). Hence, the nuclear hnRNPK at the ANXA7 promoter further connected the phospholipid-binding and hormone-related ANXA7 to the major lipidrelevant cell survival cascade and AR signaling in prostate carcinogenesis, consistent with suggested coregulation of ANXA7 and lipoxygenases (Torosyan et al, 2006). Thus, this study provides mechanistic insights into the hnRNP-associated ANXA7 control that can hinder ANXA7 cell survival regulation.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The hnRNPK level within the nuclear matrix in particular correlates with the Gleason score in prostate cancer (Barboro et al, 2009). Hence, the nuclear hnRNPK at the ANXA7 promoter further connected the phospholipid-binding and hormone-related ANXA7 to the major lipidrelevant cell survival cascade and AR signaling in prostate carcinogenesis, consistent with suggested coregulation of ANXA7 and lipoxygenases (Torosyan et al, 2006). Thus, this study provides mechanistic insights into the hnRNP-associated ANXA7 control that can hinder ANXA7 cell survival regulation.…”
Section: Discussionsupporting
confidence: 78%
“…Unlike the C-terminal with conserved annexin repeats, the unique ANXA7 N-terminal is flanked by the upstream sequences harboring an entirely different set of cis-acting and enhancer elements compared with other annexins (Shirvan et al, 1994). In our study on ANXA7 versus p53 effects on prostate cancer cells (Torosyan et al, 2006), we suggested that ANXA7 can be co-regulated by ribonucleoprotein (heterogeneous nuclear ribonucleoprotein (hnRNP)) K.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is of note that 21 tumour-suppressor genes map within either the specific or the consistently altered regions. TIMP3 and PTEN have already been reported as tumour suppressors in thyroid tumours (Hu et al, 2006;Hou et al, 2007;Wang et al, 2007), while others are involved in a variety of different tumour types, for example, TGFBR3 and ANXA7 in prostate cancer (Torosyan et al, 2006;Dong et al, 2007), TNFSF15 and TUSC1 in lung cancer (Shan et al, 2004;Hou et al, 2005), SYK and Net1 in breast cancer (Repana et al, 2006;Huang et al, 2007), SLIT1, RSU1 and KLF6 in gliomas and glioblastosmas (Chunduru et al, 2002;Dickinson et al, 2004;Camacho-Vanegas et al, 2007), DBC1 in bladder cancer (Louhelainen et al, 2006), DEC1 in oesophageal squamous cell carcinomas (Yang et al, 2005), RB1 in retinoblastoma (Corson and Gallie, 2007) and LATS2 and DLEU7 in leukaemias (Hammarsund et al, 2004;Jimenez-Velasco et al, 2005). Some of these tumour suppressors have influence on the regulation of chromatin acetylation …”
Section: Discussionmentioning
confidence: 99%
“…5-LOX increases in human colorectal tumors, and inhibition of the 5-LOX pathway suppresses the proliferation of human colon carcinoma cell lines and inhibits CRC development [56][57][58][59][60]. Dexamethasone has been reported to inhibit 5-LOX expression and its metabolite production [61,62].…”
Section: Cyclooxygenase-2 and Glucocorticoids In Tumorigenesismentioning
confidence: 99%